2021
DOI: 10.1038/s41375-021-01326-x
|View full text |Cite
|
Sign up to set email alerts
|

Activated interleukin-7 receptor signaling drives B-cell acute lymphoblastic leukemia in mice

Abstract: Activated interleukin-7 receptor signaling drives B-cell acute lymphoblastic leukemia in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 127 publications
0
14
0
Order By: Relevance
“…1 ( 31 ), and Hep3 expressing msmo1 ( 23 ) and hmgcs1 ( 23 ). The immune cell types identified included lymphocytes (expressing zap70 ( 32 ), il7r ( 33 ) and ifng1 ( 34 )), neutrophils/monocytes (expressing mmp13a ( 35 ), mmp9 ( 36 ), lyz ( 37 ) and lect2l ( 38 )), and eosinosphils (expressing viml ( 39 ), hp ( 39 ), cd81a ( 39 ) and gata2a ( 39 )). Marco ( 40 ), cxcl8a ( 41 ) and csf1ra ( 42 ) were highly expressed in noninflammatory macrophages, while grn1 ( 43 ), mpeg1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ( 31 ), and Hep3 expressing msmo1 ( 23 ) and hmgcs1 ( 23 ). The immune cell types identified included lymphocytes (expressing zap70 ( 32 ), il7r ( 33 ) and ifng1 ( 34 )), neutrophils/monocytes (expressing mmp13a ( 35 ), mmp9 ( 36 ), lyz ( 37 ) and lect2l ( 38 )), and eosinosphils (expressing viml ( 39 ), hp ( 39 ), cd81a ( 39 ) and gata2a ( 39 )). Marco ( 40 ), cxcl8a ( 41 ) and csf1ra ( 42 ) were highly expressed in noninflammatory macrophages, while grn1 ( 43 ), mpeg1 .…”
Section: Resultsmentioning
confidence: 99%
“…Nonimmune cell types primarily consisted of three hepatocyte subclusters: Hepatocyte (Hep) 1 expressing aqp12 (27) and itih2 (28), Hep 2 expressing ahsg1 (29), apoa1a (30) and apoa4b.1 (31), and Hep3 expressing msmo1 (23) and hmgcs1 (23). The immune cell types identified included lymphocytes (expressing zap70 (32), il7r (33) and ifng1 (34)), neutrophils/monocytes (expressing mmp13a (35), mmp9 (36), lyz (37) and lect2l (38)), and eosinosphils (expressing viml (39), hp (39), cd81a (39) and gata2a (39)). Marco (40), cxcl8a (41) and csf1ra (42) were highly expressed in noninflammatory macrophages, while grn1 (43), mpeg1.1 (44) and cxcr4b (45) were predominantly expressed in inflammatory macrophages.…”
Section: Single-cell Atlas Of Zebrafish Liversmentioning
confidence: 99%
“…Here, we wished to determine whether IL7RA signaling has any role in the initiation of human BCP-ALL and, if so, how the receptor activation-driven B-cell precursors are predisposed to transformation. Recent research described the ability of IL7RA activation to initiate B-cell precursor ALL 40 , 41 in mouse hematopoietic cells. However, due to the potential different functions of IL7 signaling in B-cell development in mice and humans and given the heterogeneous phenotypes of IL7RA perturbations in mice 8 11 , 42 44 , we chose to establish an experimental model that authentically re-capitulate disease initiation and progression in relevant human cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using a conditional knock-in mouse model, Almeida et al showed that physiological levels of mutant IL-7Rα were sufficient to generate preleukemic B cell precursors and to initiate leukemia resembling the human Ph-like and PAX5 P80R ALL subtypes [ 87 ]. Thomas et al generated a genetically engineered mouse model with B cell-intrinsic expression of mutant IL7R that presented with development of BCP-ALL [ 88 ]. In an elegant study, Geron et al transduced human CD34 + hematopoietic cells with mutant IL-7Rα.…”
Section: Interleukin-7 Receptor α (Il-7rα) Mutations In Bcp-all Devel...mentioning
confidence: 99%
“…These led to upregulation of IL-7R signaling (via the JAK/STAT5 or the PI3K/mTOR pathway), upregulation of oncogenes (e.g., MYC, BCL2 ), and downregulation of tumor suppressors (including IKZF1 ) [ 87 89 ]. Additionally, CDKN2A was silenced [ 89 ••], and recurrent somatic KRAS mutations which cooperate with mutant IL7R were observed [ 87 , 88 ].…”
Section: Interleukin-7 Receptor α (Il-7rα) Mutations In Bcp-all Devel...mentioning
confidence: 99%